2022
DOI: 10.2478/bioal-2022-0088
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of qNANO results from the isolation of extracellular microvesicles with the theoretical model

Abstract: Objectives: Extracellular vesicles (EVs) are heterogeneous membrane vesicles in diameter of 30-5000 nm, that transport proteins, non-coding RNAs (miRNAs), lipids and metabolites. Major populations include exosomes, ectosomes and apoptotic bodies. The purpose of this study was to compare the distribution of EVs obtained under different conditions of differential centrifugation, including ultracentrifugation, with the results developed based on a theoretical model. Methods: Immortalized endothelial cell line tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…As demonstrated by Mathilde Mathieu et al, both tetraspanins CD9 and CD63 can be released in small ectosomes formed at the plasma membrane, a finding that our results corroborate [63]. Similar observations were reported in studies performed on the immortalized endothelial cells [64].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As demonstrated by Mathilde Mathieu et al, both tetraspanins CD9 and CD63 can be released in small ectosomes formed at the plasma membrane, a finding that our results corroborate [63]. Similar observations were reported in studies performed on the immortalized endothelial cells [64].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the presence of both large and small EVs in isolated samples was confirmed not only through CryoTEM and TEM analyses but also via spectral flow cytometry, which is based on the detection of specific markers: CD9, CD63, CD81, and annexin-V. As demonstrated by Mathilde Mathieu et al, both tetraspanins CD9 and CD63 can be released in small ectosomes formed at the plasma membrane, a finding that our results corroborate [63]. Similar observations were reported in studies performed on the immortalized endothelial cells [16].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A large age variation within the group of diabetic patients (45–88) and a difference in average age between the control group (median = 50) and patients (median = 82.5) may also affect the physicochemical properties of EVs. In our previous study, we observed age has a stronger contribution in patients with CKD compared to patients without kidney disease [ 58 ]. In this study, the strong correlation of age with selected miRNAs was demonstrated.…”
Section: The Limitations Of the Studymentioning
confidence: 99%
“…We used the cellulose dialysis membrane with 1000 kDa MWCO to concentrate EVs from the urine sample, nevertheless the urinary EV sample may be slightly contaminated by Tamm Horsfall Protein (about 4% is retained), which has been visualized in our previous study using SEM imaging methods [ 59 ]. It has been described in previous articles that the applied urinary EV isolation method may also affect the yields of miRNAs [ 58 ]. After the low-pressure filtration procedure, the isolated uEV samples were frozen at -80°C.…”
Section: The Limitations Of the Studymentioning
confidence: 99%